2012
DOI: 10.1515/humor-2012-0022
|View full text |Cite
|
Sign up to set email alerts
|

Humor support in synchronous computer-mediated classroom discussions

Abstract: Computer-mediated communication (CMC), more than other media, has been associated with humor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Similarly, Ilona Vandergriff (2013) highlighted the frequency of humour, play and teasing in the interactions between native and nonnative speakers of English in her text-chat corpus. Vandergriff and Carolin Fuchs (2012) also found teasing in one of their mixed-gender dyads during an online written advanced German course. Finally, Marta González-Lloret highlighted that "in spite of their lower linguistic proficiency," L2 learners were able to communicate emotions and engage in elaborate interaction including playful language and teasing (2016,307).…”
Section: Teasing Among L2 Learners Onlinementioning
confidence: 91%
“…Similarly, Ilona Vandergriff (2013) highlighted the frequency of humour, play and teasing in the interactions between native and nonnative speakers of English in her text-chat corpus. Vandergriff and Carolin Fuchs (2012) also found teasing in one of their mixed-gender dyads during an online written advanced German course. Finally, Marta González-Lloret highlighted that "in spite of their lower linguistic proficiency," L2 learners were able to communicate emotions and engage in elaborate interaction including playful language and teasing (2016,307).…”
Section: Teasing Among L2 Learners Onlinementioning
confidence: 91%
“…By adopting the playful mode, the readers' responses, too, can function as humorous stimuli for other readers. Vandergriff & Fuchs (2012) attest that producing more humour is a prominent method of humour support in online joking. …”
Section: Adoption Of Language Playmentioning
confidence: 92%
“…Cook, 1992;Davies, 2003;Lantolf, 2000;Pomerantz & Bell, 2007;Vandergriff & Fuchs, 2009, 2012Waring, 2012;Warner, 2004). Approaching humor from a social-interactionist perspective, researchers have shown that comprehension is co-constructed in communication (Bell, 2007a(Bell, , 2007bBelz & Reinhardt, 2004;Davies, 2003;Habib, 2008;Pomerantz & Bell, 2011;Shively, 2013;Vandergriff, 2013;Vandergriff & Fuchs, 2012) and that learner understanding can be partial (Bell, 2007a(Bell, , 2007bBell & Attardo, 2010). Learners may not fully understand the intended joke if they do not know a particular lexical item or when their native culture discourages joking about certain topics (Bell, 2007a).…”
Section: L2 Humor Comprehensionmentioning
confidence: 99%
“…Research on L2 humor generally investigates learners’ ability to engage in conversational humor in face‐to‐face interactions and synchronous text‐based on‐line chats, reporting that even learners with low linguistic proficiency comprehend and produce playful talk (Bell, , ; Belz, ; Broner & Tarone, ; Bushnell, ; Cekaite & Aronsson, ; G. Cook, ; V. Cook, ; Davies, ; Lantolf, ; Pomerantz & Bell, ; Vandergriff & Fuchs, , ; Waring, ; Warner, ). Approaching humor from a social‐interactionist perspective, researchers have shown that comprehension is co‐constructed in communication (Bell, , ; Belz & Reinhardt, ; Davies, ; Habib, ; Pomerantz & Bell, ; Shively, ; Vandergriff, ; Vandergriff & Fuchs, ) and that learner understanding can be partial (Bell, , ; Bell & Attardo, ). Learners may not fully understand the intended joke if they do not know a particular lexical item or when their native culture discourages joking about certain topics (Bell, ).…”
Section: L2 Humor Comprehensionmentioning
confidence: 99%